Education, immigration and migration : policy, leadership and praxis for a changing world - Arar, Khalid; Brooks, Jeffrey S.; Bogotch, Ira (Bingley, U.K. : Emerald Publishing Limited, 2019)
Global Migration has changed the practice of educational leaders, policy makers, students, teachers and community members. This book traces this worldwide shift through research-based chapters that touch on both local idiosyncrasies and dynamics common across many contexts.Education, Immigration and Migration identifies issues educational leaders face as they seek to lead schools and school systems experiencing immigration and better understand their current strategies for improvement. The chapters shed light on the poorly understood relationship between educational leadership and refugee populations by giving a deeper appreciation of the scope and nature of issues at local, national and transnational levels. Each chapter offers new ways in which practitioners, policy-makers and scholars can think about complex dilemmas such as the implementation of equitable and democratic values, and difficulties involved in adapting organization and culture. Given its cross-national interdisciplinary approach, this book will prove invaluable for educational leaders, scholars and policymakers alike.
Prelims -- Education, immigration and migration: policy, leadership and praxis for a changing world -- Migrants, immigrants, refugees and other boxes into which we put one another -- Leadership and policy dilemmas: Syrian newcomers as future citizens of Ontario, Canada -- Leading K12 refugee integration: a gentle approach from Ontario, Canada -- Building welcoming and inclusive schools for immigrant and refugee students: policy, framework and promising praxis -- Migrant qualification recognition as control: governmentality, education and the movement of people between borders -- Leading for praxis and refugee education: orchestrating ecologies of socially just practices -- Syrian refugee students' lived experiences at temporary education centres in Turkey -- Dramatic experiences of educators coping with the influx of Syrian refugees in Syrian schools in Turkey -- Higher education for displaced Syrian refugees: the case of Lebanon -- Refugees in their own land: the challenge of managing a school in a Palestinian refugee camp in the divided city of Jerusalem -- Mediterranean migration: from treacherous seas to tortuous roads? -- Precarious realities: undocumented youth in the southwest (USA) -- Attention to the rights of students who are children of immigrant families: the case of high complexity schools in Catalonia, Spain -- Business as usual or a state of emergency? School leadership during an unprecedented increase in asylum-seekers -- The hybrid status of Muslim schools in Britain: conditions of self-expression -- Index.
Includes index.
Print version record
Keywords: Immigrant children -- Education; Refugee children -- Education; Education -- Educational Policy & Reform -- General; Organization & management of education